USSR NKGB–MGB structure - Kokurinas, Aleksandras (Genocidas ir rezistencija, 1997)
This article presents the evolution of the Soviet repressive structures: how many divisions there were and how they changed during the Stalinist period.
Keywords: Soviet Union; KGB structure